Colleges and schools-College of Agricultural Sciences and Technology-Child Family and Consumer Services 002 (1980)
Leslie Legault of Santa Maria (second from the right), pesident of California State University Beta Chi Chapter of Phi Chapter of Phi Upsilon Omicron national home economics society, presents the chapter's national Plaque Award for it's 1980-1981 professi